Pola Pengelolaan Alokasi Dana Desa (ADD) Tahun 2015 Di Negeri Batumerah Kecamatan Sirimau Kota Ambon - Nasaruddin Umar (IAIN Ambon, 2018)
This article is intended to analyze what the model of the village fund allocation 2015 in Batumerah City Ambon whether in accordance with the legislatioan. Have had the ability to draw up a financial planning and management in accordance with the provisions of the legislation in force. Ie from planning, budgeting, implementation, reporting, accountabilitiy and financial oversight village. Also discovered various inconsistensi whit that the laws regulation in force, such as the interior minister regulation number 113 of 2015 concerning the financial management of the village and regulations mayor ambon number 61 in 2014 on technical guedelines for the implementation allocation rural villages and land in the city of Ambon. Because the orientatition designation ADD 2015 state batumerah 100% dedicated to the village, dedication to the village government operation. Ie village chief fixed income, allowance village saniri, holiday allowances,operational and operational offices saniri village to improve services and community development, and boost self-help mutual aid society non achieved optimally.